INTERPRETASI TOKOH MELALUI POSTER FILM JALAN YANG JAUH JANGAN LUPA PULANG - Putra, Dhika Purnama; Saefudin, Ahmad Thabathaba’I (Universitas Mercu Buana, 2025)
Poster as one of the promotional tools that combine text and images, have an important role in film marketing strategies. Posters not only provide information, but also create emotional impressions through visual signs. In this context, posters function as a medium to convey the atmosphere and main theme of the film to potential viewers. For example, the film